Economic Status, Nutrition and Pregnancy Cost; A Vicious Cycle in Pregnancy. (29th May 2020) - Gunarathne, Sajaan; Wickramasinghe, Nuwan; Agampodi, Thilini; Prasanna, Ruwan; Agampodi, Suneth
Abstract: Objectives: Despite been in a positive pathway to achieve maternal and child healthcare targets in sustainable development goals, maternal nutrition is a leading public health problem in Sri Lanka. We studied the economic status, pregnancy expenditure and nutritional status of the pregnant mother to explore these associations. Methods: The study was carried out in Anuradhapura District, Sri Lanka. Consecutive pregnant women registered in the public health clinics and who was in the 1 st trimester of pregnancy were recruited as a part of a large cohort study. Detail evaluation of household income, expenditure and pregnancy costs were assessed together with anthropometric measurements. Results: The mean age of the pregnant women ( n  = 750) was 28.3 years (SD 5.7) and 84.6% of them have not engaged in any income-generating activities. Among the employed group, the majority (58.6%) were in the government sector. Of the 750 pregnant women, 17.3% were underweight (BMI < 18.5). The average household income of the underweight group (USD 237.56) was significantly lower (t = −2.718, P  = 0.007) than the others (USD 311.59). There was a significant difference in monthly food cost between underweight and normal mothers (t = −1.774, P  = 0.076). The average cost for food of underweight and normal mothers was USD 53.33 (SD 40.07) and USD 60.05 (SD 39.13). In addition, the pregnancy cost of underweight mothers as a fraction of the money available for food was 23.05%. Conclusions: Despite having significantly low income and low resources for food, the additional burden of pregnancy cost may be leading to a vicious cycle of undernutrition. More details and context-specific approaches are required to combat nutrition in pregnancy. Funding Sources: Accelerating Higher Education Expansion and Development (AHEAD), World Bank.